Incidence of ProTaper Universal System Instrument Fractures - A Retrospective Clinical Study - Machado, Ricardo; Souza Junior, Claudemir de; Colombelli, Matheus Felipe; Picolli, Ana Paula; Simi Junior, Jaci; Cosme-Silva, Leopoldo [UNESP]; Roberti Garcia, Lucas da Fonseca; Alberton, Luiz Romulo (Aves Press Ltd, 2018)
Objective: The aim of this retrospective clinical study was to evaluate the incidence of ProTaper UniversalSystem instrument fractures, associated with observation of the arch, group of teeth, and root thirds in which these fractures occurred. Methods: From analysis of charts, clinical record cards and radiographs of endodontic treatments performed by postgraduate students using the ProTaper Universal System at a reference center, a total of 1031 teeth and 2355 canals were analyzed. The general incidence of instrument fractures and their frequency, considering the group of teeth, arch and root thirds, were cataloged and the data obtained were statistically analyzed (Exact Fischer test, with level of significance of 1%). Results: The general percentage of fractures, considering the number of teeth and number of root canals evaluated was 4.4% and 1.9%, respectively. Instrument fractures occurred more frequently in the mandibular first (8.8%) and second (9.6%) molars, however, without statistically significant difference between them (p= 0.81). In the first and second maxillary molars, the incidence of fracture was 4.7% and 5.1%, respectively, also without significant difference (p= 0.81). Considering the dental arches (maxillary and mandibular), the fractures occurred with significantly higher frequency in the mandibular arch (66.7%), in comparison with the maxillary arch (33.3%) (p< 0.01). A significantly higher percentage of fractures occurred in the apical third (84.4%) compared with the middle third (15.6%) (p< 0.01). Conclusion: The general percentage of fractures, considering the number of teeth and number of root canals evaluated was 4.4% and 1.9%, respectively. However, the arch (mandibular) and root third (apical) had a significant effect on the incidence of instrument fractures.
Keywords: Fracture; endodontic files; nickel-titanium instruments; ProTaper universal